Uruguay : Second Review under the Stand-By Arrangement, Requests for Modification, Waiver of Nonobservance and Applicability of Performance Criteria, and Extension of Repurchase Expectations in the Credit Tranches. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Uruguay's Second Review Under the Stand-By Arrangement and Requests for Modification, Waiver of Nonobservance and Applicability of Performance Criteria are discussed. Growth remains robust, inflation is subdued, and the external position continues to strengthen, with buoyant exports and upward pressure on the peso. Fiscal performance has been better than expected, with public debt continuing to fall as a percentage of GDP. Structural reforms are also progressing well, with key new reform initiatives under way in several areas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet